The Influence of the Drama "My Mother, My Exclusive Breastfeeding Hero" on the Motivation of Exclusive Breastfeeding - Indah Dewi Ridawati; Intan Kumalasari (Babali Health, 2023)
Health education and promotion actions have been carried out at the Simpang Periuk Health Center, Lubuklinggau City by health workers, but in practice the percentage of mothers who do exclusive breastfeeding has not reached 80%. It is necessary to hold health promotion innovations in the form of drama games to touch the hearts of breastfeeding mothers so that awareness arises and strong motivation is formed to pass exclusive breastfeeding. The purpose of this study was to determine the effect of the drama "My Mother, My Exclusive ASI Hero" on the motivation to give exclusive breastfeeding to breastfeeding mothers in the work area of ​​Simpang Periuk Health Center, Lubuklinggau City. The research method used is a quasi-experimental without a control group. The sample used was 33 breastfeeding mothers with the age of the baby not exceeding 6 months by accidental sampling. The results of the Wilcoxon test showed that there was a difference in the mean value of exclusive breastfeeding motivation before and after the drama was given (p=0.000). so it could be concluded that there was a significant increase in the motivation for exclusive breastfeeding before and after the drama was given. Suggestions to the Puskesmas to be able to use the drama "My Mother is My Exclusive ASI Hero" as a method of health promotion